Atividade de estudo e capacidades do pensamento teórico análise, reflexão e planificação mental - Clarindo, Cleber Barbosa da Silva (Editora Oficina Universitária, 2020)
The first move to understand the possibilities of developing the Study Activity as a means of appropriating human capabilities is to analyze the conditions of the relationship between our historical moment and our research object. Questions such as: What are the conditions for carrying out the Study Activity in society that is based on the form of production based on the accumulation of human wealth by a few people? How to enable the development of maximum human capabilities in a society that favors and deepens social and economic inequalities between people, social, ethnic, racial and class groups? How to enable the appropriation of the most elaborate ways of thinking of human culture in children who do not have the basics to maintain their existence, such as food, housing, hygiene and clothing? These are questions that must represent the contradiction of thinking about Study Activity in capitalist society.